1963
DOI: 10.1063/1.1706737
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Liquid Flow down an Inclined Plane

Abstract: The stability of a liquid layer flowing down an inclined plane is investigated. A new perturbation method is used to furnish information regarding stability of surface waves for three cases: the case of small wavenumbers, of small Reynolds numbers, and of large wavenumbers. The results for small wavenumbers agree with Benjamin's result obtained by the use of power series expansion, and the results for the two other cases are new. The results for large wavenumbers, zero surface tension, and vertical plate contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
473
0
7

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 940 publications
(511 citation statements)
references
References 4 publications
31
473
0
7
Order By: Relevance
“…The Benney equation asymptotically predicts the linear stability threshold for the longwave hydrodynamic instability in agreement with the Orr-Sommerfeld equation, which corresponds to the exact linear stability problem of the Navier-Stokes equations (Yih 1963). It also allows for bounded nonlinear travelling-wave solutions, i.e.…”
Section: Finite-time Blow-upmentioning
confidence: 66%
“…The Benney equation asymptotically predicts the linear stability threshold for the longwave hydrodynamic instability in agreement with the Orr-Sommerfeld equation, which corresponds to the exact linear stability problem of the Navier-Stokes equations (Yih 1963). It also allows for bounded nonlinear travelling-wave solutions, i.e.…”
Section: Finite-time Blow-upmentioning
confidence: 66%
“…The stability of a single-phase falling film was first examined by Binnie (1957), Benjamin (1957) and Yih (1963). Binnie performed experiments on the onset of wave formation on a film of water flowing down a vertical wall, while Benjamin and Yih showed that the critical liquid Reynolds number beyond which instability occurs is proportional to the cotangent of the angle of inclination ft.…”
Section: Gravity-induced Instabilitymentioning
confidence: 99%
“…As a result, such systems (both closed and open) support instabilities that are not seen in two-layer flows. It has been established that two-layer flows in inclined or pressure-driven channels and single-layer free-surface flows down inclined planes, require fluid inertia for destabilisation, at least when the inclination to the horizontal is less than ninety degrees (see Chen 1995;Benjamin 1957;Yih 1963). However, in the case of two-layer free-surface flows, Kao (1968), Loewenherz & Lawrence (1989) and Chen (1993) showed that when the less viscous fluid is adjacent to the wall, then a long-wave instability can appear in the absence of inertia (zero Reynolds number); this instability has been termed inertialess instability.…”
Section: Introductionmentioning
confidence: 99%